Paleogeographic reconstruction and history of the sea level change at Sam Roi Yot National Park, Gulf of Thailand - Peerasit Surakiatchai (2019)
© 2018 by Chulalongkorn University. In this study, the paleogeography and the natural history of sea level change was reconstructed for the Sam Roi Yot National Park, Prachuap Khiri Khan, Gulf of Thailand, one of the tropical natural conservation areas. Beach ridge sand and marine shells attached to sea notches were dated by Optically Stimulated Luminescence and conventional C14 radiocarbon techniques. The paleo-landform features recognized in the inland region of the national park were a coastal bay, beach ridge plain and tombolos. The semi-circle paleo-coastal bay possibly developed at the same time as the upper sea notch, some 6,500-6,000 y ago. These inland landforms have subsequently become a tidal flat after tombolos connected the limestone islands to the mainland. This process coincided with the formation of the middle sea notch, 3,000-1,000 y ago. A total of 163 shells were collected from 10 locations with different environments, including the beach ridge, swale, tidal flat and former tidal flat. They were classified into 57 species (12 Gastropoda and 45 Bivalvia species). Anadara inaequivalvis, Anadara pilula, Saccostrea cucullata, Anomalocardia squamosal, Meretrix meretrix and Dosinia cretacea were found extensively in most areas. All these species indicated a mangrove environment to the intertidal zone.